How free is free? Retail trading costs with zero commissions - Adams, Samuel W.; Kasten, Connor; Kelley, Eric K. (Journal of Banking & Finance, 2024)
We examine the economics that underlie retail trading costs around discount brokers’ widespread adoption of zero commission trading in October 2019. Our analysis of participating brokers’ Rule 606 filings and financial statements reveals little change in payment for order flow, which suggests brokers absorbed the cost of eliminating commissions in a competitive environment. We then perform a difference-in-differences analysis of effective spreads and report economically trivial changes in retail execution costs around the commission change. Finally, we assess the total trading costs of an aggregate retail portfolio compared to a host of counterfactuals. We find that following the zero-commission change, total retail transaction costs dropped substantially even under the extreme counterfactual that these traders pay exchange quoted spreads and receive zero price improvement. Our findings support the brokerage industry's claim that dropping commissions helped retail investors and should ease regulators’ concerns to the contrary.